A Review of Wind Speed Estimation for Wind Turbine Systems Based on Kalman Filter Technique - M. Najafi Khoshrodi; Mohammad Jannati; Tole Sutikno (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This paper presents a review of wind speed estimation based on Kalman filter technique applied to wind turbine systems. Generally, wind speed measurement is performed by anemometer. The wind speed provided by the anemometer is measured at a single point of the rotor plane which is not the accurate wind speed. Also, using anemometer increases the system cost, maintenance, complexity and reduces the reliability. For these reasons, estimation of wind speed is needed for wind turbine systems. In this paper, the several wind speed estimation methods based on Kalman filter method used for wind turbine systems are reviewed.